Case report: A novel CACNA1S mutation associated with hypokalemic periodic paralysis - Nuzhnyi, Evgenii P.; Arestova, Alina S.; Rossokhin, Alexey V.; Protopopova, Anna O.; Abramycheva, Nataliya Yu; Suponeva, Natalia A.; Illarioshkin, Sergey N. (Frontiers in Neurology, 2023)
Background: Hypokalemic periodic paralysis (HypoKPP) is a rare neuromuscular genetic disorder causing recurrent episodes of flaccid paralysis. Most cases are associated with CACNA1S mutation, causing defect of calcium channel and subsequent impairment of muscle functions. Due to defined management approaches early diagnosis is crucial for promptly treatment and prevention new attacks.We report a case of HypoKPP associated with previously unreported mutation in CACNA1S gene (p.R900M). Molecular modeling of Ca V 1.1 was applied to evaluate its pathogenicity.Results: As a patient referred between attacks neurological status, laboratory and neurophysiological examination were unremarkable. Molecular modeling predicted that the p.R900M mutation affects the process of calcium channels activation.Novel CACNA1S mutation, associated with HypoKPP was identified. Monte-Carlo energy minimization of the Ca V 1.1 model supported the association of this mutation with this disease.